Differential effects of small-sided game load on neuromuscular and perceptual-cognitive performance of youth soccer players - Skala, F.; Zemková, E. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Physical and psychological load of small-sided games (SSGs) can affect players` neuromuscular and cognitive performance [1,2]. The question remains which of load variables are responsible for the impairment of performance in youth soccer players. This study investigates players` neuromuscular and perceptual-cognitive performance i) response to SSG, ii) relationship with external load and perception of fatigue.